Artificial Intelligence-Based Conceptual Change Worksheet to Reduce Misconception of Hydrostatic Pressure - Dewi Yulianawati; Asih Wahyuningsih; Mega Rizky Molidina; Muhammad Guntur Purwanto (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Pre-service elementary teachers often experience difficulties in understanding science concepts scientifically, resulting in persistent misconceptions. This condition necessitates innovative learning materials that can facilitate conceptual understanding while reducing misconceptions. This study aimed to develop an artificial intelligence-based conceptual change (AI-CoaCh) worksheet to reduce misconceptions on hydrostatic pressure among pre-service elementary teachers. The study employed the 4D development model consisting of four stages: define, design, develop, and disseminate. The participants were 30 pre-service elementary teachers in the Cirebon region. Data were collected through expert validation sheets and a four-tier diagnostic test administered before and after the implementation of the worksheet. Content validity was analyzed using the content validity ratio (CVR), while changes in students’ conceptions were analyzed based on conceptual categories identified through the four-tier diagnostic test. The results showed that the AI-CoaCh worksheet obtained a CVR score of 0.84, exceeding the critical CVR value and indicating that the worksheet met the content validity criterion. Furthermore, the number of misconceptions decreased substantially from 44 to 18 after implementation. These findings indicate that the AI-CoaCh worksheet has the potential to facilitate scientific understanding of science concepts and reduce misconceptions among pre-service elementary teachers